Performance of ventilation filtration technologies on characteristic traffic related aerosol down to nanocluster size. Issue 12 (2nd December 2017) - Karjalainen, Panu; Saari, Sampo; Kuuluvainen, Heino; Kalliohaka, Tapio; Taipale, Aimo; Rönkkö, Topi
ABSTRACT: Near traffic routes and urban areas, the outdoor air particle number concentration is typically dominated by ultrafine particles. These particles can enter into the nearby buildings affecting the human exposure on ultrafine particles indoors. In this study, we demonstrate an aerosol generation system which mimics the characteristic traffic related aerosol. The aerosol generation system was used to determine the size-resolved particle filtration efficiencies of five typical commercial filters in the particle diameter range of 1.3–240 nm. Two different HEPA filters were observed to be efficient in all particle sizes. A fibrous filter (F7) was efficient at small particle sizes representing the nucleation mode of traffic related aerosol, but its efficiency decreased down to 60% with the increasing particle size. In contrast, the filtration efficiency of an electrostatic precipitator (ESP) increased as a function of the particle size, being more efficient for the soot mode of traffic related aerosol than for the nucleation mode. An electret filter with a charger was relatively efficient (filtration efficiency >85%) at all the observed particle sizes. The HEPA, F7 and electret filters were found to practically remove the particles/nanoclusters smaller than 3 nm. All in all, the filtration efficiencies were observed to be strongly dependent on the particle size and significant differences were found between different filters. Based on these results, we suggest that the particulate filter test standards should be extended to cover the ultrafine particles, which dominate the particle concentrations in outdoor air and are hazardous for public health. Copyright © 2017 American Association for Aerosol Research